2015
DOI: 10.1074/mcp.m114.043216
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Putative Substrates for the Periplasmic Chaperone YfgM in Escherichia coli Using Quantitative Proteomics

Abstract: How proteins are trafficked, folded, and assembled into functional units in the cell envelope of Gram-negative bacteria is of significant interest. A number of chaperones have been identified, however, the molecular roles of these chaperones are often enigmatic because it has been challenging to assign substrates. Recently we discovered a novel periplasmic chaperone, called YfgM, which associates with PpiD and the SecYEG translocon and operates in a network that contains Skp and SurA. The aim of the study pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Genotyping [ 7 ] of the STM PALES_11731 mutant revealed that the mini-Tn5- tet transposon was inserted in the 3′ region of gene PALES_11731 ( yfgM ), 10 nucleotides before the end of the gene’s sequence (Additional file 1 : Figure S1). PALES_11731 codes for YfgM, an ancillary SecYEG translocon subunit [ 22 ] for which the exact function remains unclear. The insertion introduces a stop codon and the last two amino acids of the translated protein are missing (Additional file 1 : Figure S2).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping [ 7 ] of the STM PALES_11731 mutant revealed that the mini-Tn5- tet transposon was inserted in the 3′ region of gene PALES_11731 ( yfgM ), 10 nucleotides before the end of the gene’s sequence (Additional file 1 : Figure S1). PALES_11731 codes for YfgM, an ancillary SecYEG translocon subunit [ 22 ] for which the exact function remains unclear. The insertion introduces a stop codon and the last two amino acids of the translated protein are missing (Additional file 1 : Figure S2).…”
Section: Main Textmentioning
confidence: 99%
“…The predicted structure of the protein suggests that the mutation does not clearly affect the YfgM function. In Escherichia coli , an inactivation of yfgM increases the bacteria sensitivity to acidity [ 22 ]. The STM PALES_11731 mutant resistance to acid stress was, however, the same as for the wild-type strain (Additional file 1 : Table S2), supporting the idea that YfgM is still functional.…”
Section: Main Textmentioning
confidence: 99%
“…The vector encodes a T7 promoter upstream of the gene, a TEV protease cleavage site at the 3 0 end of the gene followed by a GFP folding reporter and an octahistidine tag (Norholm et al, 2013). The N-terminal tags were chosen based on their topologies and expression profiles determined in other studies (Daley et al, 2005;Lee et al, 2013;Sletta et al, 2007), membrane localization in E. coli (Gotzke et al, 2015) or relaxation of mRNA folding energy (Kudla et al, 2009). The N-terminal tag-types fall in five categories ( Fig.…”
Section: Expression Analysis Of a Library Of N-terminal Tags Of Sbcypmentioning
confidence: 99%
“…Therefore, we tested whether the previously reported YfgM interactors PpiD (31)(32)(33)(34) and RcsB (35) influence proteolysis. Because the degradation profiles were not altered in the ⌬ppiD (Fig.…”
Section: Yfgm Degradation Does Not Depend On the Presence Of Its Intementioning
confidence: 99%
“…It may mediate the transport of proteins released from the SecYEG translocon to periplasmic chaperones like SurA or Skp (32,34). On the other hand, YfgM interacts with the cytoplasmic response regulator RcsB of the Rcs phosphorelay system (35).…”
mentioning
confidence: 99%